“Tasa de crecimiento de tres gramíneas en la finca los tres potrillos.” - Cedeño Zambrano, Katherine Nicole (2020)
The following research was developed in the farm "LOS TRES POTRILLOS" located in Buena Fe canton, to evaluate the variables, their agronomic behavior, together with bromatological studies which will allow having the best results in the management of the crop, and thus provide a new food alternative in quality and forage quantity with Mombasa Grass (Megathyrsus maximus), Brachiaria (Brachiaria decumbens), Savoy (Megathyrsus maximus), these varieties of grass have been studied in the tropical areas in our country obtaining good digestibility results that benefit livestock feeding for which a Random Complete Block Design was used with 3 varieties of pastures who will be selected for their respective cuts at 21, 42, 63 days. The evaluation was carried out at 21, 42, 63 days, a review of the land was made at the beginning of the weeks, the measurement of the land and stakes were made, at 21 days the results of the first cut were obtained at 42 days the second cut 63 days after the third cut the variables to be made are plant height (cm), leaf height (cm), leaf width (cm), stem thickness (cm), root length ( cm), forage weight (g) in terms of agronomic variables with soil analysis and bromatological analysis of the Mombasa, Savoy, Brachiaria d.